The Effects of Self-Regulated Learning and School Climate on Student Well-Being through Academic Hardiness - Putri Azhar Syifa; DYP. Sugiharto; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2024)
Student well-being is a state in which students are able to develop skills and potential as well as positive self-acceptance that affects their academic performance. In this research, self-regulated learning and school climate were analyzed in terms of their effects on well-being through academic hardiness in 340 boarding Senior Islamic High School or Madrasah Aliyah (MA) in Kudus Regency selected using a proportional stratified random sampling technique. Their data were collected using the scales of self-regulated learning, school climate, students’ well-being and hardiness. Based on the findings, self-regulated learning and school climate affected students’ well-being through academic hardiness. It can be the basis for school counselors to give proper services to students.